2012
DOI: 10.1186/1755-8794-5-65
|View full text |Cite
|
Sign up to set email alerts
|

Mutation screen in the GWAS derived obesity gene SH2B1including functional analyses of detected variants

Abstract: BackgroundThe SH2B1 gene (Src-homology 2B adaptor protein 1 gene) is a solid candidate gene for obesity. Large scale GWAS studies depicted markers in the vicinity of the gene; animal models suggest a potential relevance for human body weight regulation.MethodsWe performed a mutation screen for variants in the SH2B1 coding sequence in 95 extremely obese children and adolescents. Detected variants were genotyped in independent childhood and adult study groups (up to 11,406 obese or overweight individuals and 4,5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 47 publications
3
37
0
Order By: Relevance
“…Detailed information regarding used temperatures and primers for PCR and dHPLC analysis can be obtained from the authors. All PCR amplicons with dHPLC patterns derived from the wild-type pattern were re-sequenced as described previously [8]. At least two experienced individuals independently assigned the genotypes; discrepancies were solved either by reaching consensus or by re-genotyping.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Detailed information regarding used temperatures and primers for PCR and dHPLC analysis can be obtained from the authors. All PCR amplicons with dHPLC patterns derived from the wild-type pattern were re-sequenced as described previously [8]. At least two experienced individuals independently assigned the genotypes; discrepancies were solved either by reaching consensus or by re-genotyping.…”
Section: Methodsmentioning
confidence: 99%
“…The infrequent variant allele was detected exclusively in 3 out of 11,406 obese individuals but not in 4,568 normal-weight controls [8]. When analyzing the impact of the obesity-associated SNP rs7498665 (Thr484Ala) and the rare variant βThr656Ile/γPro674Ser on STAT3-mediated leptin signaling, we did not observe functional effects [8]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…F344LfsX20A mutation causes a frameshift, resulting in production of a C-terminally-truncated SH2B1 variant lacking the entire SH2 domain [118] . A separate study reported that SH2B1 g.9483(C/T) missense mutation, but not Thr175Asp non-synonymous variant (rs147094247), is linked to obesity [119] . S H2B1 g.9483(C/T) mutation results in generation of non-synonymous SH2B1β(Thr656Ile) and SH2B1γ(Pro674Ser) variants [119] .…”
Section: Sh2b1 Regulates Reproduction In Micementioning
confidence: 99%
“…A separate study reported that SH2B1 g.9483(C/T) missense mutation, but not Thr175Asp non-synonymous variant (rs147094247), is linked to obesity [119] . S H2B1 g.9483(C/T) mutation results in generation of non-synonymous SH2B1β(Thr656Ile) and SH2B1γ(Pro674Ser) variants [119] . Four additional rare non-synonymous variants (G131S, V209I, L293R, M465T, and W649G) have been identified in Chinese populations [120] .…”
Section: Sh2b1 Regulates Reproduction In Micementioning
confidence: 99%